Hospital volumes and the likelihood of stent implantation among patients undergoing catheterization of the left heart: more is more?. (25th November 2020) - Oettinger, V; Zehender, M; Von Zur Muehlen, C; Bode, C; Kaier, K; Stachon, P
Abstract: Background: Percutaneous coronary intervention (PCI) is an established procedure, but recent studies analyzing the indication for stenting are going to change clinical practice. Previous studies suggested that hospital volume is inversely related to in-hospital mortality but its impact on likelihood of stent implantation and the number of stents remains unclear. Purpose: There is a conflict of objectives between nationwide care including short transfer and intervention times and a few large centers with maximum technology and experience. We examine the effect of hospital volume on in-hospital mortality, likelihood of stent implantation, number of stents, length of hospital stay, and reimbursement in a recent nationwide cohort from Germany. Methods: Using German national electronic health records, all patients who underwent coronary angiography with a documented coronary artery disease were identified by ICD and OPS codes. Risk-adjustment was applied using a predefined set of patient characteristics to account for differences in the risk factor composition of the patient populations between centers. Results: In 2017, a total of 528, 188 patients with a documented coronary artery disease underwent coronary angiography in Germany. Mean age was 69.8 years and 29.3% of patients were female. 55% of all patients received PCI, with a mean number of 1.01 stents implanted per patient. In-hospital mortality was 2.9%, length of hospital stay was 6.5 days and mean reimbursement was €5, 531. Multivariable regression analyses showed a positive linear association between hospital volumes and the likelihood of stent implantation (p=0.003) as well as the number of implanted stents (p=0.020). No association was found between hospital volumes and in-hospital mortality (p=0.105), length of hospital stay (p=0.201) or reimbursement (p=0.108). Inspection of the non-linear impact of procedure volumes on stent implantation practices indicates a ceiling effect in the volume-outcome relationship: implantation likelihood and number of stents per patient are lowest in centers with less than 100 procedures per year (34.4% and 0.62, respectively). Then, implantation likelihood and number of stents constantly increase until the volume category of 500 procedures per year and center. For centers with >500 procedures per year, the likelihood of stent implantation and the number of implanted stents remained relatively constant (about 60% and 1.07, respectively). Conclusion: Patients undergoing coronary angiography in low-volume centers are less frequently subject to PCI but at comparable risk for in-hospital mortality. Furthermore, the data suggest that more complex cases are treated in high volume centers with consistent mortality rates and thus constant safety is ensured in high volume hospitals. Thresholds are discussed. Funding Acknowledgement: Type of funding source: None